PROBLEM OF PLAGIARISM IN STUDENTS AND POSSIBLE WAYS TO PREVENT IT - Japaridze , Rusudan (Online Journal of Humanities ETAGTSU, 2021)
The given paper discusses the phenomenon of plagiarism, its main types and some of the basic reasons why students plagiarize. Plagiarism has always been a “headache” in all fields but it is a severe problem especially nowadays when people have access to all kinds of information on the internet and there is a temptation for students to “solve” their homework deadlines easily. Plagiarism is a big challenge in the modern world and the digitization of everything have made this process much easier. Students are novice researchers, so it is important for them to be aware of the dangers and negative consequences of misappropriation of someone else's intellectual property. It is the duty of us - teachers to inform them in this respect. The article highlights the main reasons why students might be tempted to plagiarize. Their possible solutions are also given. Full Text (PDF)